Mitochondrial Signal Transduction Abnormalities in Systemic Lupus Erythematosus - Nagy, Gyorgy; Koncz, Agnes; Phillips, Paul; Perl, Andras (Current Immunology Reviews (Discontinued), 2005)
Engagement of T cell receptors by antigen-presenting cells or stimulation by cytokines determine whether the cell will become activated, anergic or die via apoptosis or necrosis. Ca2+ is a key second messenger that delivers signal from the cell surface, reactive oxygen intermediates (ROI) and nitric oxide (NO) are recently recognized as important mediators of T-cell activation. NO as a multifunctional intracellular and intercellular messenger induces mitochondrial biogenesis in many cell types such as lymphocytes. Mitochondria produce ROI and store and release Ca2+ in response to activation and death signals. Rapid Ca2+ fluxing is increased while sustained Ca2+ signaling is decreased in lupus T cells. Lupus T cells contain increased numbers and mass of mitochondria. Serum NO levels and production of NO by monocytes is increased in patients with systemic lupus erythematosus (SLE). Lupus T cells exhibit mitochondrial hyperpolarization and increased mitochondrial mass which confer predisposition to necrosis rather than apoptosis in response to repetitive activation and death signals. Exposure of normal T cells to NO dose-dependently increase the mitochondrial mass and mimic rapid and sustained Ca2+ signal abnormalities observed in lupus T cells. Thus, increased mitochondrial biogenesis may account for altered Ca2+ handling and represents novel targets for pharmacological intervention in SLE.
Keywords: necrosis